Open diary : biography/autobiography as historical context - Greenblatt, Francine Scialom (Michaelis school of Fine Art, 2024)
Alberto Savinio in his travelogue and wartime diary "The departure of the Argonaut" (1918) graphically expressed reservations about his endeavour. "I write - that is, I lay out little black cadavres on the immaculate shroud of the page - but this doesn't begin to capture the magnificent innocence of sky and sea ..... "(1) How inadequate then does a painter feel in attempting to locate belief systems in a foreign medium that is slower than pictures? Words reduce the real experience of a painting to an approximation, and its absence constitutes a kind of willed barrier. Literary studies proposed that paintings are,independently of how they are interpreted. The nature of art works is in part determined by the art-theoretical context in which they are set. The forced shift in medium, therefore assists this author in questioning some of the familiar mental, visual and emotional landmarks by which thinking has been oriented over the past 20 years.